The development of a high-throughput acoustic droplet ejection mass-spectrometry assay and a solid-supported membrane (SSM)-based electrophysiological assay to study the pharmacological inhibition of SLC1-A3, -A2 and -A1 in a drug discovery program - Zuschlag, Yasmin; Pommereau, Antje; Warkentin, Jennifer; Licher, Thomas; Bärenz, Felix (Frontiers in Pharmacology, 2025)
IntroductionThe solute carrier (SLC) family comprises a diverse group of membrane proteins essential for transporting a variety of substrates across cellular membranes. These transporters play crucial roles in cellular homeostasis, nutrient uptake, and neurotransmitter clearance. The SLC1 subfamily, specifically SLC1A3 (EAAT1), SLC1A2 (EAAT2), and SLC1A1 (EAAT3), are excitatory amino acid transporters that regulate glutamate concentrations in the synaptic cleft, making them important targets for neurological disorder therapeutics. Despite their significance, drug discovery efforts targeting these transporters have been hampered by limitations in available screening methodologies.MethodsWe are utilizing advanced methodologies such as Acoustic Droplet Ejection Mass Spectrometry (ADE‐MS) and Solid Supported Membrane (SSM)-based electrophysiology to develop assays for the SLC1 family members: SLC1A3 (EAAT1), SLC1A2 (EAAT2), and SLC1A1 (EAAT3).Results and DiscussionIn this manuscript, we present the successful development of novel assays specifically designed for drug discovery applications targeting the SLC1 family members. Our Acoustic Droplet Ejection Mass Spectrometry (ADE‐MS) platform demonstrated high sensitivity and reproducibility in detecting substrate transport activity across all three transporters. The complementary Solid Supported Membrane (SSM)‐based electrophysiology assay provided real-time kinetic measurements of transporter function with minimal background interference. These assays exhibited Z’ factors exceeding 0.7, indicating their robustness for high-throughput screening campaigns. Initial validation using known inhibitors confirmed the assays’ ability to identify compounds with varying potencies and mechanisms of action against SLC1A3, SLC1A2, and SLC1A1.ConclusionWe endeavor to establish robust assays that can facilitate future drug discovery campaigns.